Estimación de demanda de tránsito en la carretera Florencio del Castillo, Costa Rica - Coto-Solano, María Estefanía (Instituto Tecnológico de Costa Rica, 2018)
Due to the need of updating and broadening the previous demand studies, this project aims to develop a demand study applied to the case of Florencio del Castillo road, Costa Rica. This work focuses on discovering the traffic demand in the road, whereas serving as a supply for government authorities that must make decisions about an intervention. For this purpose, demographic and socioeconomic information on the transportation zones surrounding the road was gathered. This database was systematized and filtered for its final processing, using diverse mathematical procedures. Finally, the transit demand was obtained. Thus, different upgrading proposals were evaluated to assess their impact on current traffic conditions.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2018.
Keywords: Estudio; Tránsito; Transportes; Insumos; Bases de datos; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture::Building engineering